Development of Visual Media Characteristic of Batak Culture “Dalihan Na Tolu” for Students in 6th Grade Elementary School - Defa; Wisman Hadi; Daulat Saragi (Britain International for Academic Research (BIAR) Publisher, 2020)
The research is using the 4 D Thiagarajan development model consisting of Define, Design, Development and Dissemination. The validation results of three experts consisting of material experts, design experts and media experts with a very decent category. Once validated by the three experts, the media tested on two groups of small groups and big groups by demonstrating the effectiveness of the media. One of the patterns of kinship adopted from the value of Batak culture contains many positive and good elements that can be used as a role model in the use of technology. Making the use of technology is growing by having a cultural corridor that can align in its development and use in both the digital world though. In this study gave birth to a visual learning media that collaborated with the values of Batak culture.